Pengaruh Komunikasi Internal dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT AMYTHAS - Syahdan Alfarouk; Suharini Suharini (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to determine how much influence simultaneously between internal communication and work environment on employee performance at PT AMYTHAS. This research method uses a quantitative descriptive approach with data collection techniques through distributing questionnaires to 51 respondents who are employees from various divisions. The data analysis technique uses multiple linear regression through the SPSS version 26 application. The results of the study show that partially the internal communication variable has a t-value of 2.711> Ttable 2.010 and a significance of 0.009 <0.05, so it can be concluded that internal communication has a significant effect on employee performance. Likewise with the work environment which has a t-value of 4.359> Ttable 2.010 with a significance of 0.000 <0.05, so the work environment also has a significant effect on employee performance. Simultaneously, internal communication and work environment have a significant effect on employee performance with a significance value of 0.000 <0.05 and an F count of 144.407> F table 3.19. So it can be concluded that internal communication and work environment have a joint influence on the performance of PT AMYTHAS employees.